Investigation on Aromaticity Index and Double-Bond Equivalent of Aromatic Compounds and Ionic Liquids for Fuel Desulphurization. (21st December 2013) - Abdullah, Syamsul B.; Man, Z.; Bustam, M. A.
Abstract : Aromaticity index (AI) and double-bond equivalent (DBE) were studied to seek a simpler approach in identifying suitable ionic liquids for the desulphurization process. Manifestation of interaction mechanism by COSMO-RS and Raman spectroscopy is discussed. The findings demonstrate that AI and DBE calculations can be used to analyze and arrogate potential combination of cation and anion for fuel desulphurization purposes.